McNamara’s Cephalometric Analysis of Adult Brahmins of Kathmandu - Pradhan, Resina; Rajbhandari, Anjana; Shrestha, Situ Lal (Orthodontic Journal of Nepal, 2016)
Introduction: Appropriate comparison of an individual’s craniofacial structure can be made when evaluated relative to his/her comparable peer group. However, McNamara’s Caucasian norms are being used for adult Brahmins cephalometric analysis. Objective: To determine cephalometric norms using McNamara’s analysis in adult Brahmins of Kathmandu and to compare the values within the group and with Caucasians. Materials & Method: Screening of 850 individuals aged 18-27 years was performed. Inclusion criteria were Angle’s Class I molar and canine relation with normal overjet and overbite, symmetric face with acceptable profile, without craniofacial abnormalities, orthodontic/surgical treatment in the past and without proximal caries or prosthesis. Lateral digital cephalometric radiographs of 41 selected adult Brahmins of Kathmandu (23 males and 18 females) were manually traced. Comparative test was conducted within adult Brahmins of Kathmandu and with Caucasian group at significance level p≤0.05. Result: Adult male Brahmins of Kathmandu were found to have larger craniofacial measurements: Effective Mandibular Length (p≤0.001), Maxillo-mandibular Differential (p≤0.05) and Lower Anterior Facial Height (p≤0.01) than adult female Brahmins of Kathmandu. Adult Brahmins were found to have smaller craniofacial measurements compared to Caucasians. Conclusion: Gender and ethnic diversity must be considered during orthodontic diagnosis and treatment planning for an individual.